Economic analysis of coffee cultivation in the hamlets of Alto Yacusisa and Alto Belén (José Crespo y Castillo - Huánuco - Peru) - Ticllacuri Mallqui, Amanda (2020)
Coffee is a crop that grew significantly over the decades in Peru, being even an alternative introduced more recently by the State to replace the illicit production of coca leaf. This was the situation that occurred in the hamlets of Alto Yacusisa and Alto Belén, district of José Crespo y Castillo, which belong to the Huánuco region (Peru). This work aims to perform the economic analysis of coffee cultivation in the hamlets of Alto Yacusisa and Alto Belén (District of José Crespo y Castillo, Huánuco, Peru), to measure the net revenue obtained by farmers with coffee production in 2018. For this work, in addition to the literature review and secondary data analysis, 10 coffee growers will be surveyed in each hamlet. As a result, a great variation of the profit per hectare is observed, being that 8 of the 20 producers are prejudiced in the activity. It is perceived that the fall in international coffee prices directly affects producers, in parallel to the high cost of production and low harvests. But, those who manage to contour this last point, are precisely those that obtained greater profit, as well as the producers industrialized their coffee and sold with an added value.